Tissue distribution of gamma-delta T cell subsets in oesophageal adenocarcinoma - Conroy, Melissa (My University, 2021)
The global obesity epidemic is contributing to increased prevalence of diseases fuelled by chronic inflammation, including cancer. Oesophageal adenocarcinoma (OAC) is an obesity-associated malignancy with increasing prevalence, dismal prognosis, and severely dysregulated immune processes. We previously reported that αβ T cells migrate to omentum and liver in OAC and contribute to inflammation in these tissues. Here, we assessed the tissue distribution and phenotype of gamma/delta (γδ) T cells in the blood, omentum, liver and tumour of OAC patients. Our data show that the Vδ1 and Vδ3 subsets of γδ T cells are most prevalent in omentum and liver of OAC patients. Furthermore, γδ T cells are predominantly pro-inflammatory in these tissues, and co-express IFN-γ and IL-17. Moreover, γδ T cells exhibit cytotoxic capabilities in OAC omentum and liver. This study provides the first indication that γδ T cells contribute to obesity-associated inflammation in OAC and might be exploited therapeutically.
PUBLISHED
Keywords: Inflammation; Obesity; Oesophageal adenocarcinoma; Omentum; γδ T cells; Cancer; Immunology, Inflammation & Infection; CANCER; Chronic inflamation; Immune system; Tumour immunology and immunotherapy